Cognitive Behavioral Therapy for Social Anxiety Disorder: Predictors of Treatment Outcome in a Quasi-Naturalistic Setting. Issue 2 (March 2021) - Butler, Rachel M.; O'Day, Emily B.; Swee, Michaela B.; Horenstein, Arielle; Heimberg, Richard G.
Abstract: We examined the outcomes of individual cognitive behavioral therapy (CBT) for social anxiety disorder (SAD) in a sample of 93 adults seeking treatment in a university outpatient clinic specializing in CBT for SAD. Treatment followed the structure of a manual, but number of sessions varied according to client needs. After approximately 20 weeks of therapy, patients' social anxiety had decreased and their quality of life had increased. Patients with more severe SAD or comorbid major depressive disorder (MDD) at pretreatment demonstrated higher levels of social anxiety averaged across pre- and posttreatment. However, clinician-rated severity of SAD, comorbid MDD, or comorbid generalized anxiety disorder did not predict treatment outcome. Higher pretreatment scores on measures of safety behaviors and cognitive distortions were associated with higher social anxiety averaged across pre- and posttreatment and predicted greater decreases from pre- to posttreatment on multiple social anxiety outcome measures. We found no predictors of change in quality of life. Those with high levels of safety behaviors and distorted cognitions may benefit more from CBT, perhaps due to its emphasis on targeting avoidance through exposure and changing distorted thinking patterns through cognitive restructuring methods. Our study lends support to the body of research suggesting that manualized CBT interventions can be applied flexibly in clinical settings with promising outcomes for patients over a relatively short course of therapy. Highlights: Social anxiety decreases and quality of life improves after CBT. CBT is effective in quasi-naturalistic settings. Cognitive distortions and safety behaviors predict treatment outcome.